Diagnostic Dilemma of a Widely Metastatic Gastric-type Cervical Adenocarcinoma. (9th November 2022) - Jaramillo, C; Adams, T; Shah, S; Miller, C; Teschan, N
Abstract: Introduction/Objective: Gastric-type cervical adenocarcinoma is an HPV-independent neoplasm accounting for 0.5-0.6% of cervical carcinomas, typically in women aged 50-55 years presenting with bleeding or watery vaginal discharge. The immunophenotypic and molecular overlap with mucinous pancreatic carcinomas presents a diagnostic dilemma in metastatic cases. Methods/Case Report: We report the case of a 50 year-old female with a remote history of cervical dysplasia who presented with abdominal pain in December 2020 with CT notable for an incidental prominent, heterogeneous appearing cervix. Follow-up in February-August 2021 showed two unsatisfactory pap smears and an ultrasound of the cervix revealed Nabothian cysts. A friable cervix and vaginal discharge were noted on physical exam, however, no malignancy was identified on endometrial and endocervical biopsies. The patient re-presented in March 2022 with a persistent cough and was found to have a metastatic process of unknown origin involving bilateral ovaries/lungs, abdominal mesentery, pancreas, and pelvis. Lung, cervical, endometrial, and pancreatic sampling demonstrated well- differentiated mucinous adenocarcinoma with an immunophenotype positive for CK7 and MUC6 and negative for PAX-8, CDX-2, ER, Vimentin, TTF1/Napsin, GATA-3, CK20, and p16 with wildtype p53 staining compatible with endocervical, upper gastrointestinal, or pancreaticobiliary origin. Labs were notable for elevations in CA125 (198 U/mL) and CA19-9 (4, 939 U/mL), further supporting pancreatic or gynecologic primaries. A retrospective review of all gynecologic cytology and histology specimens collected from the uterus and cervix in 2021 revealed similar bland mucinous epithelium, without overt atypia or features of malignancy. Next generation sequencing demonstrated a nonspecific and complex mutational burden including STK11 D23fs*25, SMAD4 N107fs*3, CDKN2A/B loss, KRAS G12V, and MTAP loss. Results (if a Case Study enter NA): NA Conclusion: The treatment regimens for metastatic mucinous carcinoma from the cervix and pancreas differ significantly. Ultimately, the diagnosis of widely metastatic gastric type endocervical carcinoma was made possible through extensive clinical/radiographic and retrospective pathologic correlation with the incorporation of molecular studies.